NDT TESTING USING NEUTRON RADIOGRAPHY METHOD ON PURE NICKEL COLLIMATOR FOR BNCT APPLICATION - Ricky Fajar Adiputra (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2020)
Boron neutron capture therapy (BNCT) is a targeted radiotherapy technique developed to treat patients with selected malignant tumors without any side effect. Colimator is one of important component used in BNCT. In this research collimator made by centrifugal casting processes which can cause any defect. Purpose of the research is to detect any defect in collimator made by 99% pure nickel with Neutron Radiography and processing with MNCP5 for imaging the defect. The expected result of this research is displayed an image of defect caused by centrifugal casting in collimator.